Impact of Knowledge Towards Attitudes and Perception of the LGBTQ CommunityAmong Young Adults in Malaysia - Khadijah, Mohamad Tuah; James, Wong Yun Liang (Thai Journal Online, 2023)
The focus of this study was to examine existing knowledge of Malaysian youths towards LGBTQ related concepts and issues, and how thisknowledge affectedtheir perception towards the LGBTQ communities. A customised version of theCalifornia State University, Northridge,Survey of Attitudes toward LGBT issues was used to gather data on 264 participants’ current attitudes and perception towards the LGBTQ community, and five interviewees were selected to understand the extent of their knowledge on concepts and issues about LGBTQ. Thematic analysis was used to assessqualitative data, with a subsequent cross analysis to examine the impact of their knowledge towards their attitudes and perception of the LGBTQ community. The findings of this study showed that there was a weak but positive change in attitudes and perceptionaboutLGBTQs, and that religion and cultural values remainedthe major factors contributing to participants’overall attitudes, perception,and viewpoints towards the LGBTQ community. There is huge potential to promote more accepting and inclusive attitudes towards the LGBTQ community by increasing knowledge and understanding of LGBTQ related issues and concepts.